The Integration of Management Accounting Techniques in the Functional-based Costing System - A. U. Panakhov; E. G. Babkova (Учёт. Анализ. Аудит, 2019)
With the methodological development of cost accounting, there is a transition from the spatial plane of cost grouping, which has traditionally been considered as a “functional” one, to the process evaluation. At the same time, the development of the concept of Functional-Based Costing is making a transition today from grouping costs based on structural units of an enterprise to an integral system of cost accounting methods, based on generalized functional areas of economic processes (such as automation, HR, transport logistics, R&D, compliance etc.). In the economy of an enterprise, they include a much wider range of processes rather than just the work of a specialized structural unit of that enterprise. In contrast to the previously developed costing techniques, which predominantly consisted of the new methods of cost analysis, Functional-Based Costing is not an alternative direction in management accounting methodology but is a synthetic framework that allows to integrate the results of other costing approaches that are already known and researched to date. At the same time, the functional unity of processes and resources allows us to consider the development of the approach both in the context of further dissemination of Resource Consumption Accounting as well as in the context of the development of Life Cycle Costing.